Simultaneous editing of TCR, HLA-I/II and HLA-E resulted in enhanced universal CAR-T resistance to allo-rejection - Li, Wuling; Zhu, Xiuxiu; Xu, Yanmin; Chen, Jun; Zhang, Hongtao; Yang, Zhi; Qi, Yanan; Hong, Juan; Li, Yunyan; Wang, Guixue; Shen, Junjie; Qian, Cheng (Frontiers in Immunology, 2022)
Introduction The major challenge for universal chimeric antigen receptor T cell (UCAR-T) therapy is the inability to persist for a long time in patients leading to inferior efficacy clinically. The objective of this study was to design a novel UCAR-T cell that could avoid the occurrence of allo-rejection and provide effective resistance to allogeneic Natural Killer (NK) cell rejection, together with the validation of its safety and efficacy ex vivo and in vivo. Methods We prepared T-cell receptor (TCR), Human leukocyte antigen (HLA)-I/II triple-edited (TUCAR-T) cells and evaluated the anti-tumor efficacy ex vivo and in vivo. We measured the resistance of exogenous HLA-E expressing TUCAR-T (ETUCAR-T) to NK rejection by using an enhanced NK. Furthermore, we established the safety and efficacy of this regimen by treating Nalm6 tumor-bearing mice with a repeated high-dose infusion of ETUCAR-T. Moreover, we analyzed the effects of individual gene deficiency CAR-T on treated mice and the changes in the transcriptional profiles of different gene-edited T cells via RNA-Seq. Results Data showed that HLA-II editing didn’t impair the anti-tumor efficacy of TUCAR-T ex vivo and in vivo and we found for the first time that HLA-II deficiency could facilitate the persistence of CAR-T. Contrastively, as the most commonly eliminated target in UCAR-T, TCR deficiency was found to be a key disadvantageous factor for the shorter-term anti-tumor efficacy in vivo. Our study demonstrated ETUCAR-T could effectively resist allogeneic NK rejection ex vivo and in vivo. Discussion Our research provided a potential and effective strategy for promoting the persistence of UCAR-T cells in clinical application. And it reveals the potential key factors of the poor persistence of UCAR-T along with new insights for future development.